Effect of groundwater decline on plant induced by tunnel excavation and calculation of ecological water level based on SPAC model - Xinrong Liu; Yang Zhuang; Xiaohan Zhou; Liu Liu; Hai Chen; Jingzi Deng; Bin Xu; Zhiyun Deng (Journal of Intelligent Construction, 2024)
During the excavation of tunnels in mountainous areas, groundwater may be lost, which affects the surface plants and ecology. In this article, taking Hengwu Tunnel in China as an example, based on the soil–plant–atmosphere continuum (SPAC) model, the relevant parameters were obtained by field test first, and then from the perspective of soil water matrix potential (SWMP) and soil water migration (SWM), the effect of groundwater level decline induced by mountain tunnel excavation on plant growth was studied, and the calculation method of ecological water level was put forward. The results show the following: (1) The wilting of plant roots is a dynamic process of gradual expansion from the middle of the root to both ends, and the response of SWMP in the root region to changes in atmosphere and groundwater level is lagging and non-uniform; (2) SWMP can be used to predict the degree of wilting of plant roots, while the final distribution and value of SWMP are only related to the position of the groundwater level, but not related to the decline rate of the groundwater level; (3) groundwater level and rainfall (P) will affect the value and proportion of each flux in the SPAC model, in which the relative transpiration ratio can be used to evaluate the growth of the plant and calculate the ecological water level of the plant.